2006
DOI: 10.1529/biophysj.106.081398
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of Pore-Spanning Lipid Bilayers Probed by Atomic Force Microscopy

Abstract: We measure the elastic response of a free-standing lipid membrane to a local indentation by using an atomic force microscope. Starting point is a planar gold-coated alumina substrate with a chemisorbed 3-mercaptopropionic acid monolayer displaying circular pores of very well defined and tunable size, over which bilayers composed of N,N,-dimethyl-N,N,-dioctadecylammonium bromide or 1,2-dioleoyl-3-trimethylammonium-propane chloride were spread. Centrally indenting these "nanodrums" with an atomic force microscop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
134
2
4

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 48 publications
13
134
2
4
Order By: Relevance
“…New approaches such as SLBs on nano-holes (Gonçalves et al, 2006;Steltenkamp et al, 2006) will allow a better understanding of the bilayer/substrate interaction and will permit to expose the membrane to different water phases at the two sides. For examples, the possibility to fill the holes with a gel material similar to the cell cytoplasm could reproduce a situation very similar to the biological cell case.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…New approaches such as SLBs on nano-holes (Gonçalves et al, 2006;Steltenkamp et al, 2006) will allow a better understanding of the bilayer/substrate interaction and will permit to expose the membrane to different water phases at the two sides. For examples, the possibility to fill the holes with a gel material similar to the cell cytoplasm could reproduce a situation very similar to the biological cell case.…”
Section: Conclusion and Future Trendsmentioning
confidence: 99%
“…An AFM tip can bend a freely suspended membrane, and compress a supported membrane. In recent work, Steltenkamp et al [11] showed how to extract the bending modulus of lipid bilayers from AFM force-distance curves for bilayers deposited over well defined sized holes (indentation of 'nanodrums'), in which they could safely ignore area compression due to the lack of a supported surface. Another issue neglected in previous AFM studies is the double leaflet form of lipid bilayers, which is known to influence the dynamics of fluctuations [12].…”
Section: Introductionmentioning
confidence: 99%
“…The AFM tip is modeled as a point force, as it's radius of curvature ͑of the order of 10 nm͒ is much smaller than the radius of the hole R. This differs from studies on lipid bilayer membranes, where the hole diameter is of the same order as the radius of the tip. 16 The force applied at ͑r 0 , 0 ͒ is opposed by the bending rigidity D and the tension T, which we assume to be isotropic, 17 i.e., the flake is equally stretched in both horizontal directions. The equation for deflections that are small compared to the thickness h is 11,18 ͑Dٌ 4 − Tٌ 2 ͒u͑r, ;r 0 , 0 ͒ = F tip r ␦͑r − r 0 , − 0 ͒, ͑1͒ which is solved analytically for a flake that is clamped at the edge of a circular hole ͑i.e., u͑R͒ = 0 and du / dr͑R͒ =0͒.…”
mentioning
confidence: 99%